(untitled) (Research, Society and Development, 2020)
This article aims to reflect on the ideas of the pedagogical proposal present in the work Emílio ou Educação by Jean-Jacques Rousseau (1712-1778). Research has fundamentally philosophical character, so it is theoretical and literature. In the montage, the genebrino proposes new horizons to think about the practice of the teaching and learning process. It is possible to deduce from the ideas that can be executed and learn to gain a more authentic and free aspect. Rousseau’s method takes into account the student’s learning phases according to age and ability to understand. The idea is also to preserve an original child bonding, protecting it from social vices. A proposal of gender pedagogy considers a person in his participation, that is, in addition to preparing the individual in his subjectivity, it also guides towards the formation of citizenship. Therefore, Rousseau makes us think of a possibility of education that respects individuality, the ability and the freedom to educate what the goal is the good life in all aspects.